Total Participation Management: Toward Psychological Determinants of Subjective Well-Being at Work - Katarzyna Mika; Ryszard Stocki; Agnieszka Bożek (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Aiming to determine which management practice has the strongest influence on the subjective well-being (SWB) of employees, three workplaces were assessed with reference to different levels of total participation management (TPM), an innovative approach to human resource management. The study examined whether the level of TPM is positively related with SWB, defined according to Diener’s (1984) affective and cognitive facets of work. The psychological explanation of the predicted dependence was the level of satisfaction of three basic needs (autonomy, competence and relatedness) distinguished by Deci and Ryan (2000a). The hypothesis about a positive relationship between SWB and TPM was confirmed. Results indicate that the least participative company has employees with the lowest subjective well-being and with the lowest satisfaction of basic psychological needs.